1981
DOI: 10.3758/bf03202017
|View full text |Cite
|
Sign up to set email alerts
|

A single-transient masking paradigm

Abstract: Visual masking, as typically studied in the twotransient paradigm (Matin, 1975), involves suppression of the visibility of one brief stimulus, the target, by another (spatio-jtemporally contiguous brief stimulus, the mask. Recent neurophysiologically based theories of visual masking rely on the existence, in the higher mammalian visual system, of short-latency, fast transient channels which inhibit longer latency, slower sustained channels (for review, see Breitmeyer & Ganz, 1976). In particular, recent theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…These characteristics are shared by another transient-induced phenomenon, where a transient stimulus triggers fading of an object presented in the periphery (Kanai and Kamitani 2003;Moradi and Shimojo 2004; see also Breitmeyer and Rudd 1981;Wilke et al 2003). The fading effect shows the time-locked characteristics.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These characteristics are shared by another transient-induced phenomenon, where a transient stimulus triggers fading of an object presented in the periphery (Kanai and Kamitani 2003;Moradi and Shimojo 2004; see also Breitmeyer and Rudd 1981;Wilke et al 2003). The fading effect shows the time-locked characteristics.…”
Section: Discussionmentioning
confidence: 95%
“…Third, adaptation to the dominant perceptual interpretation is necessary, and the strength of the effect depends on the depth of adaptation. Breitmeyer & Rudd, 1981). The fading effect shows the time-locked characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Since both the Troxler effect (Clarcke, 1957(Clarcke, , 1961 and visual masking (Breitmeyer & Rudd, 1981) increase with eccentricity, we examined the effect of this variable with CD in Experiment 4.…”
Section: Experiments 4 Eccentricity Effectsmentioning
confidence: 99%
“…Traditionally, this phenomenon has been investigated by the presentation of targets and masking stimuli for brief periods while relative time (interstimulus interval [ISI] or stimulus onset asynchrony [SOA] ) and order of presentation (e.g., paracontrast or metacontrast) are varied. However, one study (Breitmeyer & Rudd, 1981) also demonstrated that a continuously viewed stimulus can be abruptly removed from conscious awareness by the brief presentation of nearby masking stimuli. This implies that disappearance need not involve local adaptation.…”
mentioning
confidence: 99%
“…Critically, all subjects in all three experiments had obvious type A metacontrast functions.2 Clearly, our "single transient stimuli" are very different from those ofBreitmeyer and Rudd (1981), where masking effects on a very long duration target are demonstrated. Although not identical, they bear some similarity to those ofBellefeuille and Faubert (1998), in which a certain proportion of pixels reversed polarity from frame to frame.3 After completion of the four randomized conditions of Experiment 1, participants first ran one session of Experiment 3, then Experiment 2 (one session), then another session of Experiment 3, all within a week.…”
mentioning
confidence: 97%